Auditor Independence and Value Relevance in the European Banking Sector: Do Investor Protection Environment and Corporate Governance Matter?. (July 2022) - Cimini, Riccardo; Mechelli, Alessandro; Sforza, Vincenzo
Our study explores the effects of statutory auditor's independence on value relevance, measuring the different impact against the quality of country-level investor's protection and firm-level corporate governance. A sample of 98 European financial entities listed on the stock markets of 15 countries in the period from 2009 to 2014 is used to measure statutory auditor independence by taking into account audit firm tenure, partner tenure, and the percentage of nonaudit fees. Findings demonstrate that in different investor protection environments or in the presence of differences in corporate governance quality, phenomena that could be interpreted as a deterioration of the auditor independence do not necessarily determine a decrease in the value relevance of accounting numbers. Rather, they may determine a possible increase if the knowledge spillover effects prevail over the perception that independence has deteriorated. These findings add to the literature and provide regulators with insights by suggesting that not only accounting and auditing practices but also country features or firm-level corporate governance quality might influence the outcome of reforms on the independence of the statutory auditor as well as value relevance judgments.